Analisis Media Komunikasi Live Streaming dalam Membangun Minat Konsumen terhadap Produk Alawiyahijab - Annisa Sayyidatul Aulia; Chika Salzabila Damayanti; Muhammad Kamalludin; Siti Mahmudah Noorhayati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The current increase in technological development is a very rapid development, which is very significant. One of them can be seen from the variety of communication media which makes it quite easy for people to communicate with each other, namely via voice or even live video. Likewise, in the world of entrepreneurs or businesspeople, quite a few people use social media as a means of introducing various products for sale. Some special social media applications used by entrepreneurs are those that can immediately do live streaming, which is one of the most effective and efficient ways to market the products they sell. Live streaming media has a significant direct influence on consumer trust, which means consumer trust is considered to be important in online sales. Even though the trend of using marketing via live streaming media can be a big hope for the income of user entrepreneurs, it is necessary to pay attention to privacy and cyber security in order to always avoid and/or minimize these problems.